From near extinction to diversification by means of a shift in pollination mechanism in the gymnosperm relict Ephedra (Ephedraceae, Gnetales). (29th January 2016) - Bolinder, Kristina; Humphreys, Aelys M.; Ehrlén, Johan; Alexandersson, Ronny; Ickert‐Bond, Stefanie M.; Rydin, Catarina
Abstract : Pollination in gymnosperms is usually accomplished by means of wind, but some groups are insect‐pollinated. We show that wind and insect pollination occur in the morphologically uniform genus Ephedra (Gnetales). Based on field experiments over several years, we demonstrate distinct differences between two Ephedra species that grow in sympatry in Greece in pollen dispersal and clump formation, insect visitations and embryo formation when insects are denied access to cones. Ephedra distachya, nested in the core clade of Ephedra, is anemophilous, which is probably the prevailing state in Ephedra . Ephedra foeminea, sister to the remaining species of the genus, is entomophilous and pollinated by a range of diurnal and nocturnal insects. The generalist entomophilous system of E. foeminea, with distinct but infrequent insect visitations, is in many respects similar to that reported for Gnetum and Welwitschia and appears ancestral in Gnetales. The Ephedra lineage is well documented already from the Early Cretaceous, but the diversity declined dramatically during the Late Cretaceous, possibly to near extinction around the Cretaceous–Palaeogene boundary. The clade imbalance between insect‐ and wind‐pollinated lineages is larger than expected by chance and the shift in pollination mode may explain why Ephedra escaped extinction and began to diversify again.